Clinical Practice Guidelines for Acute Pericarditis Treatment - Félix Rolando Jorrín Román; Lázaro De la Cruz Aviles; Roberto Vega Hernández; Francisco Riverón Mena (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Clinical Practice Guidelines for Acute Pericarditis Treatment. It has been defined as a syndrome caused by the inflammation of the pericardium for diverse aetiologies. The etiological agents, clinical presentation, diagnostic methods and steps that must be taken are described in this document. It includes assessment guidelines focused on the most important aspects to be accomplished.